2012
DOI: 10.1002/pmic.201100601
|View full text |Cite
|
Sign up to set email alerts
|

SRM targeted proteomics in search for biomarkers of HCV‐induced progression of fibrosis to cirrhosis in HALTC patients

Abstract: The current gold standard for diagnosis of hepatic fibrosis and cirrhosis is the traditional invasive liver biopsy. It is desirable to assess hepatic fibrosis with noninvasive means. Targeted proteomic techniques allow an unbiased assessment of proteins and might be useful to identify proteins related to hepatic fibrosis. We utilized Selected Reaction Monitoring (SRM) targeted proteomics combined with an organ-specific blood protein strategy to identify and quantify 38 liver-specific proteins. A combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…Five proteins (A1BG, CFH, IGFALS, PROC, and RBP4) were identified and verified with selected reaction monitoring as potential serum biomarkers that separate HCVinfected patients from healthy individuals or distinguish HCV patients at different stages of fibrosis (30). All five proteins were detected with significant differential abundance in our analysis, and observed with the same expression trends.…”
Section: Functional Classification and Comparison With Previousmentioning
confidence: 53%
“…Five proteins (A1BG, CFH, IGFALS, PROC, and RBP4) were identified and verified with selected reaction monitoring as potential serum biomarkers that separate HCVinfected patients from healthy individuals or distinguish HCV patients at different stages of fibrosis (30). All five proteins were detected with significant differential abundance in our analysis, and observed with the same expression trends.…”
Section: Functional Classification and Comparison With Previousmentioning
confidence: 53%
“…We found that alpha-1-B-glycoprotein (A1BG) and T4 surface glycoprotein precursor (TSGP) were both up-regulated in DEW and SP, and the expression was over two-fold higher in SP than DEW (Figure 1; Table 1). A1BG was reportedly involved in a number of diseases such as endometrial cancer, cervical cancer and cervical squamous cell carcinoma (30), and was also elevated in hepatic fibrosis patients, which allowed such patients to be easily distinguished from HI (31). TSGP was associated with T-cell costimulation, positive regulation of interleukin-2 biosynthesis, T-cell receptor complex formation, extracellular matrix structural constituents, the transmembrane receptor protein tyrosine kinase signaling pathway, early endosomes, innate immune responses, and proteinaceous extracellular matrix and MHC class II protein complexes.…”
Section: Glycoproteinsmentioning
confidence: 99%
“…Blood contains organ-specific gene products that are released into circulation through tissue damage, enzymatic cleavage from the cell membrane, or normal blood secretion, providing a source of clinically useful biomarkers for differentiating normal from diseased organs (15). A comparison with published human tissue expression atlases (data on deep comparative transcriptome analyses of multiple organs) (16)(17)(18) showed that 130 of the 320 neuron-specific genes from Cahoy et al (3), of which our 170 genes are a subset, are n = 3 genes*, Accuracy = 80%*** n = 2 genes*, Accuracy = 80%*** n = 3 genes**, Accuracy = 79%*** n = 2 genes**, Accuracy = 76%*** n = 12 genes*, Accuracy = 89%*** n = 6 genes, Accuracy = 74%*** n = 12 genes, Accuracy = 64%*** Gene Ontology gene sets with consistent differences in relative gene expression (reordering of gene set components) between clusters.…”
Section: Transcriptomic Signatures Distinguishing Cortical and Noncormentioning
confidence: 99%